Study on the Fractal Characteristics of Coal Body Fissure Development and the Law of Coalbed Methane Migration of around the Stope. (22nd July 2020) - Yang, He; Liu, Zhen; Zhu, Danliang; Yang, Wenzhi; Zhao, Dawei; Wang, Wendi
Abstract : Due to the complicated coalbed methane (CBM) occurrence conditions and the diverse geological structures in China, the promotion and application of the coal and gas simultaneous extraction technology have been seriously restricted. In view of this, this paper chooses Qingdong Coal Mine protection layer mining and CBM extraction field practice as the research background. Firstly, based on the similar material simulation experiment that simulates coal mining, the dynamic changing pattern of a mining field's overburdened strata and corresponding stress are obtained, the relationship between gas desorption and stress can then be clarified. Further, with the help of the fractal theory and box counting method, the fracture development characteristics of the overlying strata are quantitatively described on the basis of experimental images. Finally, by building a model for calculating the penetrability coefficient of coal seam based on fractal dimension of mining fissure and analyzing the relationship between fissure development and fractal dimension, the gas migration law and the fissure development areas of #7 and #8 overburden strata where CBM concentrates can be revealed and determined. According to the orientation of the area mentioned above, the location of the CBM pumping field in relation to the coal seam roof and the arrangement of CBM extraction boreholes can be optimized, which make CBM extraction efficient. Meanwhile, the risk of coal and gas outburst is significantly reduced when the CBM concentration is controlled within 0.2% to 0.6% outside the corner of the working face and 0.1% to 0.35% in return flow, which is lower than 0.8%, the threshold of CBM concentration.